The role of flexibility and optimality in the prediction of intracellular fluxes of microbial central carbon metabolism - Tarlak, Fatih; Sadikoglu, Hasan; Çakır, Tunahan (Royal Soc Chemistry, 2014)
Prediction of intracellular metabolic fluxes based on optimal biomass assumption is a well-known computational approach. While there has been a significant emphasis on the optimality, cellular flexibility, the co-occurrence of suboptimal flux distributions in a microbial population, has hardly been considered in the related computational methods. We have implemented a flexibility-incorporated optimization framework to calculate intracellular fluxes based on a few extracellular measurement constraints. Taking into account slightly suboptimal flux distributions together with a dual-optimality framework (maximization of the growth rate followed by the minimization of the total enzyme amount) we were able to show the positive effect of incorporating flexibility and minimal enzyme consumption on the better prediction of intracellular fluxes of central carbon metabolism of two microorganisms: E. coli and S. cerevisiae.
Keywords: Genome-Scale Reconstruction; Escherichia-Coli; Saccharomyces-Cerevisiae; Transcriptional Regulation; Objective Functions; Balance Analysis; Bacillus-Subtilis; Pathway Analysis; Systems Biology; Optimal-Growth